Studi Toksisitas Nanopartikel Organ Limpa pada Hewan Percobaan, Tinjauan Scoping Review - Dodi Faras Ilmiawan Sutomo; Dwi Nur Ahsani; Ika Fidianingsih (Fakultas Farmasi Universitas Pancasila, 2022)
Nanotechnology has been developing in the medical field, but some nanoparticles have toxic effects on the body, including the spleen. This scoping review represents an attempt to take stock of existing research results related to the presence or absence of toxicity to the spleen caused by nanoparticles involving experimental animals. A scoping review was conducted to synthesize and map the toxicity of nanoparticles. It has been searched on PubMed databases for spleen or lien and toxic or toxicity, and nanoparticles or dendrimers or